Oxytocin Attenuates Expression, but Not Acquisition, of Sucrose Conditioned Place Preference in Rats - Patel, Devon; Sundar, Megana; Lorenz, Eva; Leong, Kah-Chung (Frontiers in Behavioral Neuroscience, 2020)
Maladaptation of reward processing for natural rewards, such as sucrose or sugar, may play a role in the development of diseases such as obesity and diabetes. Furthermore, uncovering mechanisms to disrupt or reverse maladaptation of reward-seeking behaviors for natural reinforcers can provide insight into treatment of such diseases, as well as disorders such as addiction. As such, studying the effects of potential pharmacotherapeutics on maladaptive sugar-seeking behavior offers valuable clinical significance. Sucrose conditioned place preference (CPP) paradigms can offer insight into aspects of reward processes as it provides a way to assess acquisition and expression of context-reward associations. The present study examined the effect of peripheral oxytocin injections on sucrose CPP in rats. Oxytocin, when administered prior to CPP test, attenuated expression of sucrose CPP. However oxytocin, when administered during sucrose conditioning, did not affect subsequent place preference. These findings suggest oxytocin sufficiently attenuates expression of sucrose-associated place preference.